The prevalence and associated factors of self-reported symptoms of computer vision syndrome among high school teachers in Riyadh: A cross-sectional study - Afnan Younis; Laila Alsabbagh; Dimah Alaraifi; Ghaida Alsanad; Ahad Algrain; Rema AlDihan; Fatimah Albassam (Journal of Nature and Science of Medicine, 2022)
Background: Computer vision syndrome (CVS) is a group of visual and musculoskeletal symptoms that are associated with the use of computers and electronic devices. The use of computers is increasing in the field of education which puts teachers at higher risk of CVS. The severity of CVS symptoms can affect teachers' quality of life and productivity. Aim: This study aims to estimate the prevalence of CVS and its symptoms among Riyadh high school teachers in 2020. The secondary objectives were to determine the factors associated with CVS among high school teachers and to compare between the symptoms of CVS in male and female school teachers. Subjects and Methods: This is an observational cross-sectional study. Data were collected by self-administered questionnaire from teachers working in public high schools in Riyadh, Saudi Arabia, using a multistage random sampling technique. Data analysis including descriptive statistics and Chi-square test was performed using SPSS. Results: The prevalence of experiencing one or more symptoms of CVS among high school teachers was 94.6%. The most common symptom was neck and shoulder pain, reported by 84.9% of high school teachers. Male teachers were 80% less likely to have CVS (odds ratio [OR] = 0.213, 95% confidence interval [CI] [0.079–0.578]). The risk of CVS was higher in those who use electronic devices for more than 5 h (OR = 3.4, 95% CI [1.015–11.4]). Male teachers experienced less headache (OR = 0.504, 95% CI [0.344–0.75]), less neck and shoulder pain (OR = 0.326, 95% CI [0.186–0.57]), and less eyestrain (OR = 0.495, 95% CI [0.308–0.796]) in comparison to female teachers. Conclusion: Female high school teachers are having higher odds of developing CVS than male teachers. School teachers need awareness programs about CVS.